Contribution to the biological study of versenos (Foreword) - Guzmán Barrón, Alberto (1956)
The Versed is ethylene diamine acid tetracélico whose corboxílicos groups can be neutralized by cations, becoming the versenatos. If you reach the organism Versenate sodium, extracellular fluid calcium replaces sodium as accomplished Versenate calcium eliminated by the kidney, causing transient hypocalcaemia. Also, if adequate calcium Versenate doses are injected, this cation can be replaced by other metals (lead, copper, mercury, zinc, vanadium. Etc.), property which can be used to remove toxic metals that have managed to settle in organism.